The knowledge necessary for educational and evaluation practice in school physical education (Research, Society and Development, 2021)
This work aims to present the application of teaching methodologies and strategies, more specifically adopted in the teaching journey. The design of this work was based on the Bibliographic Research of a qualitative nature, based on literature review studies on pedagogical practices and assessment methods. Within the concepts of Tardif (2002) the teacher's personality is an essential component of their work. Let's call it invested or lived work, indicating, with this expression, that a teacher cannot “just do his job”, he must also commit and invest in this work what he is as a person. For several authors, a good content assessment can bring beneficial and gradual results during the learning and knowledge acquired by students, however, these assessments need to be chosen and applied in the student's daily life in order to lead them to learning, thus obtaining satisfactory results from its assessment and avoiding erroneous analyzes and stress on the part of educators and students.